2017
DOI: 10.15644/asc51/4/1
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Assessment of Croatian Dental Medicine Students on Their Knowledge and Skills in Prosthodontics

Abstract: ObjectivesThe aim of the study was to establish the subjective perception of dental medicine students' knowledge and skills in prosthodontics and to determine both how their perception changed during their study, by gaining clinical experience. Also, the aim was to investigate if there were any socio-demographic factors that influenced students' perception.MethodsThe research, based on an anonymous survey for dental medicine students was carried out at the School of Dental Medicine, University of Zagreb in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(17 reference statements)
2
2
0
Order By: Relevance
“…In one study, male students showed better clinical skills than female students, while there were no statistically significant differences in their theoretical knowledge (Kelsey et al, 2009). However, another study (Dulčić et al, 2017) not find any such impact, which was consistent with the findings of our study. Dentistry is a field of science that requires knowledgebased attention.…”
Section: Discussionsupporting
confidence: 90%
“…In one study, male students showed better clinical skills than female students, while there were no statistically significant differences in their theoretical knowledge (Kelsey et al, 2009). However, another study (Dulčić et al, 2017) not find any such impact, which was consistent with the findings of our study. Dentistry is a field of science that requires knowledgebased attention.…”
Section: Discussionsupporting
confidence: 90%
“…As mentioned earlier, dentists expressed the least satisfaction with “Fixed Prosthodontics”, “Mobile Prosthodontics” and “Orthodontics”. The results of the current study were confirmed by another study conducted in Croatia and other studies from different parts of the world 7,13,14,20 . The dissatisfaction of students who graduated in Croatia is most likely since fixed prosthetic restorations are only partially covered by financial resources of the Croatian Health Insurance Fund, and the patients themselves must pay for all major work.…”
Section: Discussionsupporting
confidence: 81%
“…The results of the current study were confirmed by another study conducted in Croatia and other studies from different parts of the world. 7,13,14,20…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the perception of greater knowledge and skills in students at higher years of study is not surprising. Previous studies showed that students in higher years of study perceive greater knowledge and/or skills, such as in orofacial pain [ 17 ], dental implants [ 18 ], or prosthodontics [ 19 ], than their colleagues with fewer years of study. Therefore, academic progress and experience appear to positively influence perceived competencies.…”
Section: Discussionmentioning
confidence: 99%